Synthesis and electrochemical performance of an imidazolium based Li salt as electrolyte with Li fluorinated sulfonylimides as additives for Li-Ion batteries. (10th April 2019) - Ahmed, Faiz; Rahman, Md. Mahbubur; Sutradhar, Sabuj Chandra; Lopa, Nasrin Siraj; Ryu, Taewook; Yoon, Sujin; Choi, Inhwan; Lee, Yonghoon; Kim, Whangi
Abstract: Herein, we report the synthesis of a novel imidazolium-based ionic salt, lithium (fluorosulfonyl) ((3-(1-methyl-1H-imidazol-3-ium-3-yl)propyl)sulfonyl) bis(fluorosulfonyl)imide (LiFSMIPFSI) as an electrolyte for the application in lithium-ion battery (LIB). The as-synthesized LiFSMIPFSI exhibited high purity and yield, which was characterized by various spectroscopic techniques. The LiFSMIPFSI electrolyte with a mixed solvent of ethylene carbonate (EC) and dimethyl sulfoxide (DMSO) (75:25 v/v) showed a wide electrochemical stability (ca. 4.5 V vs. Li/Li + ) and high thermal stability (300 °C), good Li + conductivity (ca. 8.02 mS/cm at 30 °C), and low intrinsic viscosity, which concurrently delivered a specific discharge capacity of ca. 125 mAhg −1 at 0.1 C with the full LIB configuration of LiFePO4 /electrolytes/graphite. The performance of this LiFSMIPFSI electrolyte was enhanced further by the addition of conventional lithium bis(fluoro-sulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) ionic salts (20% each) as additives with the specific discharge capacity of ca. 147 and 139 mAhg −1, respectively, at 0.1 C. This is mainly due to the additional enhancement of Li + conductivity and its concentrations in the electrolytes induced by the additives. The LiFSMIPFSI electrolyte with LiFSI additive based LIB showed the highest cycling stability (capacity retention ca. 97%) among the electrolytes after 500 charge-discharge cycles. Thus, the present work contributes to the development of new ionic salts and its effects upon the addition of additives on LIB performance. Graphical abstract: Image 1 Highlights: Imidazolium-based ionic salt (LiFSMIPFSI) was prepared as an electrolyte for LIBs. LiFSMIPFSI electrolyte showed good ionic conductivity and LIB performance. LiFSI and LiTFSI were added as additives to enhance the performance of LiFSMIPFSI. LiFSMIPFSI with LiFSI additive delivered a maximum capacity of 147 mAhg −1 . The electrolyte without/with additives showed good capacity retention.